THE IMPLEMENTATION OF GENRE - BASED APPROACHFOR THE TEACHING OF ENGLISHAT SMA MUHAMMADIYAH 1 KLATEN - Wahyuningsih, Neny (2007)
This current study aims at describing the implementation of Genre-based Approach at SMA Muhammdiyah 1 Klaten. The objective of this current study is know the teaching learning process at SMA Muhammadiyah 1 Klaten using Genre-based Approach. In this study, the writer uses an ethnographic research which describes the implementation of Genre-based Approach in teaching English. The methods of collecting data are observation, interview and documentation. The procedures for analyzing data are reducing, display and verifying. The result of this research shows the objective of learning, the model of syllabus, the material of English teaching, the classroom procedure, classroom activities in every stage, and problem faced by the teacher. The writer finds that classroom procedure uses two procedures namely BKOF-MOT- JCOT-ICOT BKOF-MOT-ICOT. In every stage there are many activities. The activities in BKOF are asking question and giving explanation. In MOT the teacher gives example of the text. In JCOT, the activity is the teacher makes a group. And activities in ICOT are giving the task in the classroom and giving the task as homework. The research also shows the problems faced by the teacher, namely difficulty in managing the class, the students' limited vocabulary and students' difficulty in writing coherence text. Genre-based Approach makes the teacher easier to deliver the material. The implementation of Genre-based Approach which is used by the teacher does not always use the stages of Genre-based Approach.